Schistosoma mansoni: descoberta de novos genes e estudos de genômica funcional de uma RHO GTPase - Tulio Marcos Santos (2000)
Schistosoma mansoni is a digenetic trematode that causes schistosomiasis, a parasitic disease that constitutes an important public health problem in Brazil and in many other countries throughout the world. The S. mansoni genome project was started in 1992 as a Brazilian initiative to discover new genes of this parasite for new drugs and vaccine development. At the debut of the program, hundreds of Expressed Sequence Tags (EST) were generated from an adult worm cDNA library. However, S. mansoni has a complex life cycle, which made necessary to expand the gene discovery program to other developmental stages of the parasite. In the present work, eight libraries from distinct developmental stages, all constructed using the ZapII system, were excised "en masse" to obtain double strand cDNA templates and generate large numbers of ESTs from each one of them. The quality of the transcripts from the excised libraries was then evaluated. At least 30 colonies from each library were selected to evaluate the average size of the inserts by PCR. Most of them had an average insert size greater than 500 bp. Most of them were shown to have less than 20% useless clones and more than 50% new genes. When considering only genes presents in more than one library, a total of 466 unique genes were obtained, corresponding to 427 new S. mansoni genes. From the total of unique genes, 20.2% were identified based on homology with genes from other organisms, 8.3% matched S. mansoni characterized genes and 71.5% represent unknown genes. After these initial evaluations, our efforts were directed to cercaria, the parasite larval form which infects humans and other vertebrates. Two S. mansoni cercarial cDNA libraries were examined and partial sequences obtained from 957 randomly selected clones. Based on homology searches, 551 (57.6%) ESTs generated had no homologs in the public databases while 308 (32.2%) were putatively identified, totaling 859 informative ESTs. The remaining 98 (10.2%) were uninformative ESTs (ribosomal RNA and non-coding mitochondrial sequences). By clustering analysis we were able to identify 453 different genes. One hundred and nineteen identified genes were sorted into 11 functional categories where genes associated with energy metabolism were the most abundant (13%) and diverse. The diversity and abundance of genes associated with the transcription-translation machinery and with regulatory-signaling functions were also noticeable. A paramyosin transcript was identified, indicating that this gene is not exclusively expressed in adult worms and sporocysts (as had been suggested previously). Among the new genes discovered, we identified a S. mansoni Rho-type GTP-binding gene, which was entirely sequenced in this work. The gene open reading frame was 579 bp long and encoded a putative 193 amino acid polypeptide with an estimated molecular weight of 21.8 kDa. The deduced amino acid sequence was highly homologous to the Rho GTPases of several species and contained all Rho-type GTPase conserved domains. S. mansoni Rho GTPase gene (SMRHO) overexpression complements a Sacharomyces cerevisiae rho1 null mutant strain. The complementation is seen even in high temperature and Ca2+ concentration conditions which are restrictive for the yeast growing. However, some phenotypical alterations, such as cell cycle arrest, cell enlargement, and random budding, were also observed indicating that S. mansoni Rho GTPase could not complement suitably all functions performed by the wild type RHO1 GTPase of S. cerevisiae. The complementation results of a knockout S. cerevisiae strain with SMRHO gene along with sequence alignments made evident that a higher conservation of specific amino acid residues at á3-helix loop7 region of the S. mansoni Rho GTPase protein may explain the complementation seen even in high temperature and Ca2+ concentration conditions. Our results demonstrate that ESTs are a very versatile and efficient approach for gene discovery in the different developmental stages of the S. mansoni life cycle and that S. cerevisiae may be a powerful alternative for gene function investigations in this complex parasite.